STRATEGI PENGEMBANGAN OBYEK WISATA LEMBAH HIJAU DI KELURAHAN MALINO KABUPATEN GOWA - baya, Nur (UNIVERSITAS NEGERI MAKASSAR, 2019)
ABSTRACTÂ The results of the study show that the supporting factors in Lembah Hijau tourism objects are very supportive for further development, while the shortcomings that need to be considered and taken seriously so as not to hamper the development of the Green Valley. In addition, the strategies that need to be taken in the development of the Lembah Hijau tourism object are new innovations and cooperation in the three main elements, namely managers, government and society.